Method for preparing perovskite light-emitting diode by low-pressure auxiliary solution method
By introducing low-voltage auxiliary solution method and polymer interface layer technology into perovskite light emitting diodes, the internal defects and carrier imbalance of perovskite light emitting diodes in the prior art are solved, and efficient electro-optical conversion and stability are achieved.
Patent Information
- Application Number
- CN202411737554.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2044-11-29
AI Technical Summary
In the prior art, the solution method of the perovskite light emitting diodes has problems such as luminescence quenching caused by internal defects and non-radiation loss caused by carrier imbalance, and the process cost is high and the environmental pollution is large.
The perovskite light emitting diode was prepared by low-pressure auxiliary solution method. By setting a polymer interface layer between the perovskite light emitting layer and the electron transport layer, and processing in a low-pressure environment of 1×10-1mbar, the processing time was finely adjusted to optimize the performance of the interface layer.
It effectively avoids high-temperature annealing treatment steps, prevents the electron transport layer from eroding the perovskite luminescent layer, suppresses the interface loss phenomenon, significantly improves the electron transport efficiency and composite luminescent performance, and improves the electro-optical conversion efficiency and stability of the device.
Smart Images

Figure CN119562739A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of optoelectronic materials and relates to a method for preparing a perovskite light-emitting diode using a low-pressure auxiliary solution method. Background Art
[0002] Perovskite light-emitting diode (PeLED) is a new electro-optical conversion technology based on perovskite light-emitting layer. With its high extinction coefficient, high carrier mobility, high quantum efficiency, adjustable bandgap, low material cost and compatibility with roll-to-roll process, it has application potential in near-infrared display, communication and biology. However, most PeLEDs use thermal deposition to prepare the electron transport layer on top of the perovskite layer. In order to achieve low-cost PeLED and its scalable preparation, the all-solution device process is the most urgent problem to be solved.
[0003] Although the solution method for preparing perovskite light-emitting diodes has many advantages, there are inevitably some challenges in this process. For example, the morphology and structure of perovskite nanocrystals are difficult to control, which directly affects the performance of the device; the large amount of organic solvents required in the preparation process not only increases the cost, but also may pollute the environment; some solvents may corrode the perovskite layer, causing serious photoluminescence quenching, thereby weakening the performance and stability of the device, seriously limiting the wide application of PeLED.
[0004] In addition, research on improving effective carrier injection and transport, efficient light-emitting layer structure design, and optimizing interface energy levels has scientific guiding value for improving the performance of PeLED devices. Since the perovskite light-emitting layer is very critical in the device's electro-optical conversion, especially by suppressing the crystal defects of the light-emitting layer and improving the balanced transport of carriers in the semiconductor functional layer to achieve effective composite luminescence, it is of great significance for the development of low-cost PeLED. Summary of the invention
[0005] The present invention aims to solve the problems and defects in the above-mentioned prior art. The present invention provides a method for preparing perovskite light-emitting diodes by a low-pressure assisted solution method, which is used to solve the problem that the perovskite light-emitting diodes prepared by the solution method in the prior art are luminescence quenching caused by internal defects and non-radiative losses caused by carrier imbalance, while improving the energy relationship of each functional layer, thereby improving the luminous efficiency of the device.
[0006] In a first aspect, the present invention provides a method for preparing a perovskite light-emitting diode by a low-pressure assisted solution method, comprising: providing an interface layer between a perovskite light-emitting layer and an electron transport layer of the perovskite light-emitting diode;
[0007] The PEI organic solution was spin-coated on the perovskite light-emitting layer, so that the gas pressure was reduced to 1×10 -1mbar or less, maintain the air pressure, and let it stand and dry to obtain the interface layer.
[0008] Furthermore, the present invention dissolves PEI in isopropanol to obtain the PEI organic solution, and the concentration of the PEI organic solution is 0.2 mg / mL;
[0009] The spin coating has a rotation speed of 2000 to 5000 rpm / min, and the spin coating time is 50 to 60 s;
[0010] The static drying time is 0.5 to 1 hour.
[0011] Furthermore, the present invention adopts a solution method to sequentially spin-coat a hole transport layer, a perovskite light-emitting layer, an interface layer and an electron transport layer on an anode substrate;
[0012] Then, a cathode modification layer and a cathode are sequentially vacuum-evaporated on the electron transport layer.
[0013] Furthermore, the anode substrate of the present invention is treated with continuous ultrasonic cleaning with deionized water, anhydrous ethanol, acetone and isopropanol in sequence for at least 20 to 30 minutes each;
[0014] Then, the anode substrate is subjected to surface treatment;
[0015] The surface treatment is any one of plasma bombardment surface treatment and ultraviolet light treatment.
[0016] Furthermore, the hole transport layer of the present invention is prepared by spin coating PEDOT:PSS and then annealing;
[0017] The PEDOT:PSS is a PEDOT:PSS solution and water ultrasonically mixed in a volume ratio of 1:1 for 2 hours;
[0018] The spin coating speed is 2000-4000 rpm / min, and the spin coating time is 50-60 s;
[0019] The annealing temperature is 130-150° C., the annealing time is 15-20 min, and the annealing environment is air.
[0020] Furthermore, the perovskite light-emitting layer of the present invention is prepared by spin coating a perovskite precursor solution and then heat treating it;
[0021] The perovskite precursor solution is prepared by dissolving CsBr, PbBr2 and P123 in DMF or DMSO;
[0022] The spin coating rotation speed is 2000-4000 rpm / min, the spin coating time is 50-60 s, and the spin coating environment is nitrogen;
[0023] The heat treatment temperature is 50-80° C., the heat treatment time is 1-3 min, and the heat treatment environment is nitrogen.
[0024] The mass ratio of CsBr, PbBr2 and P123 is 8.33:8.3:0.3.
[0025] Furthermore, the electron transport layer of the present invention is prepared by spin coating of TPBi solution;
[0026] The TPBi solution is TPBi dissolved in DMF or DMSO, and the concentration of the TPBi solution is 3-5 mg / mL;
[0027] The rotation speed of the spin coating is 1000-3000 rpm / min, and the spin coating time is 50-65 s.
[0028] Furthermore, the cathode modification layer of the present invention is LiF, and the thickness of the cathode modification layer is 0.3-1 nm;
[0029] The cathode is any one of metal silver and aluminum, and the thickness of the cathode is 80-150 nm.
[0030] Furthermore, the present invention provides a method for preparing a perovskite light-emitting diode by a low-pressure assisted solution method, and the specific operations are as follows:
[0031] S1. The anode substrate is an ITO substrate or a FTO substrate. The anode substrate is placed in deionized water, anhydrous ethanol, acetone and isopropanol for ultrasonic cleaning in turn. The ultrasonic cleaning time for each time is 20 to 30 minutes. After the ultrasonic cleaning, the anode substrate is dried. Then, the dried anode substrate is surface treated, i.e., plasma bombardment surface treatment or ultraviolet light treatment, to achieve further cleaning.
[0032] S2. PEDOT:PSS solution and water were ultrasonically mixed at a volume ratio of 1:1 for 2 hours. The mixed PEDOT:PSS solution was filtered through a 0.22 μm aqueous filter head and then dripped onto the anode substrate. A hole transport layer film was then formed by spin coating at a rotation speed of 2000-4000 rpm / min for 50-60 seconds. After spin coating, the film was annealed at 130-150°C for 15-20 minutes in an air environment.
[0033] S3. The perovskite precursor solution is prepared by dissolving CsBr, PbBr2 and P123 in N,N-dimethylformamide or dimethyl sulfoxide in a mass ratio of 8.33:8.3:0.3. In a nitrogen environment of a glove box, spin-coat the perovskite precursor solution at a speed of 2000-4000 rpm / min for 50-60 seconds. After spin coating, continue to heat treat in a nitrogen environment at a temperature of 50-80°C for 1-3 minutes.
[0034] S4. PEI organic solution is PEI dissolved in isopropanol with a concentration of 0.2 mg / mL. The spin coating speed of PEI organic solution is 2000-5000 rpm / min, and the spin coating time is 50-65 s. After the spin coating is completed, vacuum treatment is performed for 5-30 min to make the air pressure 1×10 -1 mbar, and then let it stand in a vacuum environment for 0.5 to 1 h.
[0035] S5.TPBi solution is TPBi dissolved in DMF or DMSO, the concentration of TPBi solution is 3-5 mg / mL, the spin coating speed of TPBi solution is 1000-3000 rpm / min, and the spin coating time is 50-60 s.
[0036] S6. The vacuum-evaporated cathode modification layer is LiF, and the thickness of the cathode modification layer is 0.3-1 nm. The vacuum-evaporated cathode is metallic silver or aluminum, and the thickness of the cathode is 80-150 nm.
[0037] In a second aspect, the present invention provides a perovskite light emitting diode.
[0038] Furthermore, the perovskite light-emitting diode of the present invention comprises a hole transport layer, a perovskite light-emitting layer, an interface layer, an electron transport layer, a cathode modification layer and a cathode which are sequentially arranged on an anode substrate.
[0039] Compared with the prior art, the technical solution provided by the present invention has at least the following beneficial effects or advantages:
[0040] The present invention introduces a low-pressure processed polymer interface layer technology to achieve a 1×10 -1In a low-pressure environment of 100 mbar, the low-pressure treatment time is finely regulated and optimized. This method effectively avoids the high-energy-consuming high-temperature annealing treatment step in the traditional process, solves the technical problem of thin film curing, and effectively prevents the electron transport layer from corroding the perovskite light-emitting layer. In addition, the method described in the present invention also suppresses the interface loss phenomenon, significantly improves the electron transport efficiency and composite luminescence performance. The perovskite light-emitting device prepared by the method described in the present invention not only has high electro-optical conversion efficiency, but also has excellent stability. The present invention achieves precise optimization of the performance of the interface layer by precisely controlling the processing time and the low-pressure environment, simplifies the preparation process of the perovskite light-emitting diode, and reduces the preparation cost. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] Figure 1 Schematic diagram of the structure of a perovskite light-emitting diode.
[0042] Figure 2 Schematic diagram of the structure of PEI molecule.
[0043] Figure 3 This is the JV curve of the perovskite light-emitting diode.
[0044] Figure 4 This is the LV curve of the perovskite light-emitting diode. DETAILED DESCRIPTION
[0045] The technical scheme of the present invention is described below in conjunction with the embodiments, but the present invention is not limited to the following embodiments. The experimental methods and detection methods described in each embodiment are conventional methods unless otherwise specified; the reagents and materials described are all commercially available unless otherwise specified.
[0046] Example 1
[0047] This embodiment provides a method for preparing a perovskite light-emitting diode using a low-pressure assisted solution process.
[0048] This embodiment provides a perovskite light emitting diode, such as Figure 1 As shown, the structure of the perovskite light-emitting diode includes: a hole transport layer, a perovskite light-emitting layer, an interface layer, an electron transport layer, a cathode modification layer and a cathode, which are sequentially arranged on the anode substrate; each functional layer of the perovskite light-emitting diode described in this embodiment is made by solution spin coating.
[0049] The method for preparing the perovskite light-emitting diode described in this embodiment comprises the following steps:
[0050] (1) Cleaning and drying the anode substrate;
[0051] (2) spin coating PEDOT:PSS on the surface of the anode substrate described in step (1) and annealing to obtain a hole transport layer;
[0052] (3) spin coating a perovskite precursor solution on the hole transport layer described in step (2), and obtaining a perovskite light-emitting layer after heat treatment;
[0053] (4) spin coating the PEI organic solution on the perovskite light-emitting layer described in step (3), and vacuum drying to obtain an interface layer;
[0054] (5) spin coating the TPBi solution on the interface layer described in step (4) to prepare an electron transport layer;
[0055] (6) Vacuum evaporating a cathode modification layer and a cathode on the electron transport layer described in step (5).
[0056] Wherein, the anode substrate in the step (1) is an ITO substrate or a FTO substrate, and the anode substrate is placed in deionized water, anhydrous ethanol, acetone and isopropanol for ultrasonic cleaning in sequence, and the ultrasonic time for each time is 20 to 30 minutes. After the ultrasonic treatment, the anode substrate is dried, and then the dried anode substrate is surface treated, i.e., plasma bombardment surface treatment or ultraviolet light treatment, to achieve further cleaning.
[0057] The PEDOT:PSS (poly(3,4-ethylenedioxythiophene)-poly(styrene sulfonate)) in step (2) is a PEDOT:PSS solution and water in a volume ratio of 1:1, and the mixing time is 2 hours. The mixed PEDOT:PSS solution is filtered through a 0.22 μm aqueous filter head and then dripped onto the anode substrate, and then a hole transport layer film is formed by spin coating, with a rotation speed of 2000 to 4000 rpm / min and a spin coating time of 50 to 60 seconds. After the spin coating is completed, annealing is performed at 130 to 150° C. in an air environment for 15 to 20 minutes.
[0058] The perovskite precursor solution in step (3) is prepared by dissolving CsBr, PbBr2 and P123 (polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer) in N,N-dimethylformamide (DMF) or dimethyl sulfoxide (DMSO) in a mass ratio of 8.33:8.3:0.3. In a nitrogen environment of a glove box, the perovskite precursor solution is spin-coated at a speed of 2000-4000 rpm / min and a spin-coating time of 50-60 s. After the spin coating is completed, heat treatment is continued in a nitrogen environment at a temperature of 50-80°C and a heat treatment time of 1-3 min.
[0059] The PEI (polyethyleneimine) organic solution in step (4) is PEI dissolved in isopropanol at a concentration of 0.2 mg / mL, wherein the molecular structure of PEI is as follows Figure 2 The spin coating speed of the PEI organic solution is 2000-5000 rpm / min, and the spin coating time is 50-65 s. After the spin coating is completed, a vacuum treatment is performed for 5-30 min to make the air pressure 1×10 - 1 mbar, and then let it stand in a vacuum environment for 0.5 to 1 h.
[0060] The TPBi (1,3,5-tris(1-phenyl-1H-benzimidazol-2-yl)benzene) solution in step (5) is TPBi dissolved in DMF or DMSO, and the concentration of the TPBi solution is 3 to 5 mg / mL. The spin coating speed of the TPBi solution is 1000 to 3000 rpm / min, and the spin coating time is 50 to 60 s.
[0061] The vacuum-evaporated cathode modification layer in step (6) is LiF, and the thickness of the cathode modification layer is 0.3-1 nm. The vacuum-evaporated cathode is metallic silver or aluminum, and the thickness of the cathode is 80-150 nm.
[0062] Example 2
[0063] This embodiment provides a method for preparing a perovskite light-emitting diode using a low-pressure assisted solution process.
[0064] The structure of the perovskite light-emitting diode device provided in this embodiment is the same as that in Embodiment 1, namely, anode (ITO) / hole transport layer (PEDOT:PSS:deionized water) / perovskite light-emitting layer / interface layer (PEI organic solution) / electron transport layer (TPBi) / / cathode modification layer (LiF) / cathode (Ag).
[0065] 1. Cleaning of anode ITO substrate
[0066] The ITO substrate was ultrasonically cleaned in deionized water, anhydrous ethanol, acetone and isopropanol in turn, and the ultrasonic time was 20 minutes each time. After the ultrasonic treatment, the ITO substrate was dried in an oven for more than 2 hours to ensure that the ITO substrate was completely dry and ready for use. The cleaned and dried ITO substrate was treated with ultraviolet light for 5 minutes to facilitate the uniform distribution of the hole transport layer solution on the ITO substrate.
[0067] 2. Preparation of hole transport layer
[0068] (1) Preparation of hole transport layer solution: Take out the PEDOT:PSS solution from a 4°C refrigerator, leave it for half an hour until the solution returns to room temperature, mix deionized water and the PEDOT:PSS aqueous solution in a volume ratio of 1:1 to obtain a hole transport layer solution.
[0069] (2) Preparation of hole transport layer: The hole transport layer solution was filtered through a 0.22 μm aqueous filter head and then dropped onto the ITO substrate. The solution was spin-coated at a speed of 3000 rpm / min for 60 s and then annealed in air at 130° C. for 20 min. The thickness of the hole transport layer was 10 nm.
[0070] 3. Preparation of perovskite light-emitting layer
[0071] (1) Preparation of perovskite precursor solution: CsBr, PbBr2 and P123 reagents were mixed in a mass ratio of 83.3:8.3:0.3 and dissolved in DMSO to obtain a perovskite precursor solution.
[0072] (2) Preparation of perovskite light-emitting layer: Figure 1 The stacking order of the device structure shown is that the ITO substrate coated with the hole transport layer is transferred into the glove box and spin-coated with the perovskite precursor solution. The spin coating amount is 75 μL, the spin coating speed is 2000 rpm / min, and the spin coating time is 60 s. Then, heat treatment is performed at a temperature of 60°C for 1.5 min. The thickness of the perovskite light-emitting layer is 20 nm.
[0073] 4. Preparation of the Interface Layer
[0074] (1) Preparation of interface layer solution: PEI was dissolved in isopropanol to prepare a PEI organic solution with a concentration of 0.2 mg / mL.
[0075] (2) Preparation of interface layer: After the perovskite light-emitting layer was prepared, the interface layer was treated in the glove box. The spin coating amount was 75 μL of isopropanol liquid, the spin coating speed was 4000 rpm / min, and the spin coating time was 60 s. Then, the existing device (i.e., anode / hole transport layer / perovskite light-emitting layer / interface layer) was placed in a small transition chamber of the glove box and vacuumed for 5 min to a pressure of 1×10 -1 mbar, and allowed to stand for 1 h to dry.
[0076] 5. Preparation of Electron Transport Layer
[0077] (1) Preparation of electron transport layer solution: The electron transport material TPBi was dissolved in DMSO to prepare a TPBi solution with a concentration of 5 mg / mL.
[0078] (2) Preparation of electron transport layer: After the interface layer is prepared, the device is transferred from the small transition chamber to the glove box to prepare the electron transport layer. The spin coating amount is 75 μL, the spin coating speed is 2000 rpm / min, and the spin coating time is 60 s.
[0079] 6. Preparation of cathode modification layer and cathode
[0080] After the electron transport layer is prepared, the device is transferred into a vacuum evaporation chamber for evaporation of the cathode modification layer (LiF) and the cathode (Ag), wherein the thickness of the evaporated cathode modification layer is 1 nm, and the thickness of the evaporated cathode is 100 nm.
[0081] 7. Electrical performance characterization
[0082] After the silver electrode cathode evaporation is completed, the device is placed in a glove box for characterization of electrical properties, namely the device's current, voltage, brightness, efficiency and other electrical properties.
[0083] Example 3
[0084] This embodiment provides a method for preparing a perovskite light-emitting diode using a low-pressure assisted solution process.
[0085] On the basis of Example 2, during the preparation of the interface layer, the existing device (i.e., anode / hole transport layer / perovskite light-emitting layer / interface layer) was placed in a small transition chamber of a glove box and vacuumed for 10 minutes to a pressure of 1×10 -1 mbar, and allowed to stand for 1 h to dry.
[0086] Example 4
[0087] This embodiment provides a method for preparing a perovskite light-emitting diode using a low-pressure assisted solution process.
[0088] On the basis of Example 2, during the preparation of the interface layer, the existing device (i.e., anode / hole transport layer / perovskite light-emitting layer / interface layer) was placed in a small transition chamber of a glove box and vacuumed for 20 minutes to a pressure of 1×10 -1 mbar, and allowed to stand for 1 h to dry.
[0089] Example 5
[0090] This embodiment provides a method for preparing a perovskite light-emitting diode using a low-pressure assisted solution process.
[0091] On the basis of Example 2, during the preparation of the interface layer, the existing device (i.e., anode / hole transport layer / perovskite light-emitting layer / interface layer) was placed in a small transition chamber of a glove box and vacuumed for 30 minutes to a pressure of 1×10 -1mbar, and allowed to stand for 1 h to dry.
[0092] Example 6
[0093] This embodiment provides a method for preparing a perovskite light-emitting diode using a low-pressure assisted solution process.
[0094] The structure of the perovskite light-emitting diode device provided in this embodiment is the same as that in Embodiment 1.
[0095] 1. Cleaning of anode FTO substrate
[0096] The FTO substrate was ultrasonically cleaned in deionized water, anhydrous ethanol, acetone and isopropanol in turn, and the ultrasonic time was 30 minutes each time. After the ultrasonic treatment, the FTO substrate was dried in an oven for more than 2 hours to ensure that the FTO substrate was completely dry and ready for use. The cleaned and dried FTO substrate was treated with plasma bombardment for 5 minutes to facilitate the uniform distribution of the hole transport layer solution on the FTO substrate.
[0097] 2. Preparation of hole transport layer
[0098] (1) Preparation of hole transport layer solution: Take out the PEDOT:PSS solution from a 4°C refrigerator, leave it for half an hour until the solution returns to room temperature, mix deionized water and the PEDOT:PSS aqueous solution in a volume ratio of 1:1 to obtain a hole transport layer solution.
[0099] (2) Preparation of hole transport layer: The hole transport layer solution was filtered through a 0.22 μm aqueous filter head and then dropped onto the FTO substrate. The solution was spin-coated at a speed of 2000 rpm / min for 50 s and then annealed in air at 150° C. for 15 min.
[0100] 3. Preparation of perovskite light-emitting layer
[0101] (1) Preparation of perovskite precursor solution: CsBr, PbBr2 and P123 reagents were mixed in a mass ratio of 83.3:8.3:0.3 and dissolved in DMF to obtain a perovskite precursor solution.
[0102] (2) Preparation of perovskite light-emitting layer: Figure 1 The stacking order of the device structure shown is that the FTO substrate coated with the hole transport layer is transferred into the glove box and spin-coated with the perovskite precursor solution. The spin coating amount is 75 μL, the spin coating speed is 4000 rpm / min, and the spin coating time is 50 s. Then, a heat treatment process is performed at a temperature of 50°C and heating for 1 min.
[0103] 4. Preparation of the Interface Layer
[0104] (1) Preparation of interface layer solution: PEI was dissolved in isopropanol to prepare a PEI organic solution with a concentration of 0.2 mg / mL.
[0105] (2) Preparation of interface layer: After the perovskite light-emitting layer was prepared, the interface layer was treated in the glove box. The amount of PEI organic solution used for spin coating was 75 μL, the spin coating speed was 2000 rpm / min, and the spin coating time was 50 s. Then, the existing device (i.e., anode / hole transport layer / perovskite light-emitting layer / interface layer) was placed in a small transition chamber of the glove box and vacuumed for 30 min to a pressure of 1×10 -1 mbar, and allowed to stand for 0.5 h to dry.
[0106] 5. Preparation of Electron Transport Layer
[0107] (1) Preparation of electron transport layer solution: The electron transport material TPBi was dissolved in DMF to prepare a TPBi solution with a concentration of 3 mg / mL.
[0108] (2) Preparation of electron transport layer: After the interface layer is prepared, the device is transferred from the small transition chamber to the glove box to prepare the electron transport layer. The spin coating amount is 75 μL, the spin coating speed is 1000 rpm / min, and the spin coating time is 50 s.
[0109] 6. Preparation of cathode modification layer and cathode
[0110] After the electron transport layer is prepared, the device is transferred into a vacuum evaporation chamber for evaporation of the cathode modification layer (LiF) and the cathode (Al), wherein the thickness of the evaporated cathode modification layer is 0.3 nm, and the thickness of the evaporated cathode is 80 nm.
[0111] The external quantum efficiency of the perovskite light-emitting diode prepared in this embodiment is 2.1%, and the brightness is 3670 cd / m 2 .
[0112] Example 7
[0113] This embodiment provides a method for preparing a perovskite light-emitting diode using a low-pressure assisted solution process.
[0114] The structure of the perovskite light-emitting diode device provided in this embodiment is the same as that in Embodiment 1.
[0115] 1. Cleaning of anode ITO substrate
[0116] The ITO substrate was ultrasonically cleaned in deionized water, anhydrous ethanol, acetone and isopropanol in turn, and the ultrasonic time for each time was 30 minutes. After the ultrasonic treatment, the ITO substrate was dried in an oven for more than 2 hours to ensure that the ITO substrate was completely dry and ready for use. The cleaned and dried ITO substrate was treated with ultraviolet light for 5 minutes to facilitate the uniform distribution of the hole transport layer solution on the ITO substrate.
[0117] 2. Preparation of hole transport layer
[0118] (1) Preparation of hole transport layer solution: Take out the PEDOT:PSS solution from a 4°C refrigerator, leave it for half an hour until the solution returns to room temperature, mix deionized water and the PEDOT:PSS aqueous solution in a volume ratio of 1:1 to obtain a hole transport layer solution.
[0119] (2) Preparation of hole transport layer: The hole transport layer solution was filtered through a 0.22 μm aqueous filter head and then dropped onto the ITO substrate. The solution was spin-coated at a speed of 4000 rpm / min for 50 s and then annealed in air at 150° C. for 15 min.
[0120] 3. Preparation of perovskite light-emitting layer
[0121] (1) Preparation of perovskite precursor solution: CsBr, PbBr2 and P123 reagents were mixed in a mass ratio of 83.3:8.3:0.3 and dissolved in DMSO to obtain a perovskite precursor solution.
[0122] (2) Preparation of perovskite light-emitting layer: Figure 1 The stacking order of the device structure shown is that the ITO substrate coated with the hole transport layer is transferred into the glove box and spin-coated with the perovskite precursor solution. The spin coating amount is 75 μL, the spin coating speed is 4000 rpm / min, and the spin coating time is 50 s. Then, a heat treatment process is performed at a temperature of 80°C for 3 minutes.
[0123] 4. Preparation of the Interface Layer
[0124] (1) Preparation of interface layer solution: PEI was dissolved in isopropanol to prepare a PEI organic solution with a concentration of 0.2 mg / mL.
[0125] (2) Preparation of interface layer: After the perovskite light-emitting layer was prepared, the interface layer was treated in the glove box. The amount of PEI organic solution used for spin coating was 75 μL, the spin coating speed was 5000 rpm / min, and the spin coating time was 50 s. Then, the existing device (i.e., anode / hole transport layer / perovskite light-emitting layer / interface layer) was placed in a small transition chamber of the glove box and vacuumed for 30 min to a pressure of 1×10 -1 mbar, and allowed to stand for 0.5 h to dry.
[0126] 5. Preparation of Electron Transport Layer
[0127] (1) Preparation of electron transport layer solution: The electron transport material TPBi was dissolved in DMSO to prepare a TPBi solution with a concentration of 3 mg / mL.
[0128] (2) Preparation of electron transport layer: After the interface layer is prepared, the device is transferred from the small transition chamber to the glove box to prepare the electron transport layer. The spin coating amount is 75 μL, the spin coating speed is 3000 rpm / min, and the spin coating time is 50 s.
[0129] 6. Preparation of cathode modification layer and cathode
[0130] After the electron transport layer is prepared, the device is transferred into a vacuum evaporation chamber for evaporation of the cathode modification layer (LiF) and the cathode (Ag), wherein the thickness of the evaporated cathode modification layer is 0.3 nm, and the thickness of the evaporated cathode is 150 nm.
[0131] The external quantum efficiency of the perovskite light-emitting diode prepared in this embodiment is 2.2%, and the brightness is 3885 cd / m 2 .
[0132] Example 8
[0133] This example provides the electrical performance of a perovskite light-emitting diode prepared by a low-voltage assisted solution method.
[0134] The present invention tests the electrical properties of the perovskite light-emitting diodes prepared in Examples 2 to 5, such as current density, voltage, current efficiency, and brightness, to obtain corresponding curves.
[0135] The current density-voltage curve is as follows Figure 3 As shown in the figure, with the increase of low-pressure pumping time of the interface layer PEI organic solution, the current density shows an upward trend. This is because PEI evaporates more and has a lower concentration. The interface layer plays a good role in suppressing interface losses and improving energy relations, promoting the effective recombination of carriers, and changing the electrical properties of the diode device.
[0136] Brightness-voltage curve Figure 4 As shown in the figure, the device brightness increases significantly with the increase of the low-pressure pumping time of the interface layer PEI organic solution. In this process, the concentration of the interface layer solution first changes the thickness and density of PEI in the interface layer. When the concentration of the PEI organic solution is low, the interface layer plays a good role in suppressing interface loss and improving energy relations, promoting the effective recombination of carriers, and significantly improving the device brightness.
[0137] The embodiments described above are part of the embodiments of the present invention, but not all of them. The detailed description of the embodiments of the present invention is not intended to limit the scope of the invention claimed for protection, but only represents selected embodiments of the present invention. All other embodiments obtained without creative work and related deductions and substitutions made by ordinary technicians in the field under the conditions of the concept of the present invention belong to the scope of protection of the present invention.
Claims
1. A method for preparing a perovskite light-emitting diode by a low-pressure assisted solution method, characterized in that: include: providing an interface layer between the perovskite light-emitting layer and the electron transport layer of the perovskite light-emitting diode; The PEI organic solution was spin-coated on the perovskite light-emitting layer, so that the gas pressure was reduced to 1×10 -1 mbar or less, maintain the air pressure, and let it stand and dry to obtain the interface layer.
2. The method according to claim 1, characterized in that Dissolving PEI in isopropanol to obtain the PEI organic solution, wherein the concentration of the PEI organic solution is 0.2 mg / mL; The spin coating has a rotation speed of 2000 to 5000 rpm / min, and the spin coating time is 50 to 60 s; The static drying time is 0.5 to 1 hour.
3. The method according to claim 1, characterized in that include: A hole transport layer, a perovskite light emitting layer, an interface layer and an electron transport layer are prepared by spin coating on an anode substrate in sequence by a solution method; Then, a cathode modification layer and a cathode are sequentially vacuum-evaporated on the electron transport layer.
4. The method according to claim 3, characterized in that The anode substrate is sequentially subjected to continuous ultrasonic cleaning with deionized water, anhydrous ethanol, acetone and isopropanol for at least 20 to 30 minutes each; Then, the anode substrate is subjected to surface treatment; The surface treatment is any one of plasma bombardment surface treatment and ultraviolet light treatment.
5. The method according to claim 3, characterized in that: The hole transport layer is prepared by spin coating PEDOT:PSS and then annealing; The PEDOT:PSS is a PEDOT:PSS solution and water ultrasonically mixed in a volume ratio of 1:1 for 2 hours; The spin coating speed is 2000-4000 rpm / min, and the spin coating time is 50-60 s; The annealing temperature is 130-150° C., the annealing time is 15-20 min, and the annealing environment is air.
6. The method according to claim 3, characterized in that The perovskite light-emitting layer is prepared by spin coating a perovskite precursor solution and then heat treating it; The perovskite precursor solution is prepared by dissolving CsBr, PbBr2 and P123 in DMF or DMSO; The spin coating rotation speed is 2000-4000 rpm / min, the spin coating time is 50-60 s, and the spin coating environment is nitrogen; The heat treatment temperature is 50-80°C, the heat treatment time is 1-3 minutes, and the heat treatment environment is nitrogen; The mass ratio of CsBr, PbBr2 and P123 is 8.33:8.3:0.
3.
7. The method according to claim 3, characterized in that The electron transport layer is prepared by spin coating of TPBi solution; The TPBi solution is TPBi dissolved in DMF or DMSO, and the concentration of the TPBi solution is 3-5 mg / mL; The rotation speed of the spin coating is 1000-3000 rpm / min, and the spin coating time is 50-65 s.
8. The method according to claim 3, characterized in that The cathode modification layer is LiF, and the thickness of the cathode modification layer is 0.3-1 nm; The cathode is any one of metal silver and aluminum, and the thickness of the cathode is 80-150 nm.
9. A perovskite light-emitting diode, characterized in that: Prepared by the method according to any one of claims 1 to 8.
10. The perovskite light-emitting diode according to claim 9, characterized in that: The invention comprises a hole transport layer, a perovskite light-emitting layer, an interface layer, an electron transport layer, a cathode modification layer and a cathode which are sequentially arranged on an anode substrate.
Citation Information
Patent Citations
Perovskite nanocrystalline light-emitting device with double interface modification layers and preparation method of perovskite nanocrystalline light-emitting device
CN112786800A
Blue-light perovskite thin film, preparation thereof, and inverted quasi-two-dimensional blue-light perovskite light-emitting diode
CN113130802A
Perovskite solar cell manufacturing method
CN113285028A
Near-infrared light emitting diode and preparation method thereof
CN116709798A